2021
DOI: 10.1038/s41388-021-01754-0
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the glucocorticoid receptor signature gene Mono Amine Oxidase-A enhances the efficacy of chemo- and anti-androgen therapy in advanced prostate cancer

Abstract: Despite increasing options for treatment of castration-resistant prostate cancer, development of drug resistance is inevitable. The glucocorticoid receptor (GR) is a prime suspect for acquired therapy resistance, as prostate cancer (PCa) cells are able to increase GR signaling during anti-androgen therapy and thereby circumvent androgen receptor (AR)-blockade and cell death. As standard AR-directed therapies fail to block the GR and GR inhibitors might result in intolerable side effects, the identification of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…With the rapid development of genomics, a large number of genomic data were obtained from the microarray chip and high-throughput sequencing, which helped us to better understand the tumor heterogeneity and guide future clinical decision-making ( Miyamoto et al, 2018 ; Labrecque et al, 2019 ; Puhr et al, 2021 ; Ylitalo et al, 2021 ). For example, the SPP1 gene was identified as an extracellular matrix signature, which was remarkably up-regulated in mCRPC and may be a novel therapeutic target for mCRPC patients ( Pang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of genomics, a large number of genomic data were obtained from the microarray chip and high-throughput sequencing, which helped us to better understand the tumor heterogeneity and guide future clinical decision-making ( Miyamoto et al, 2018 ; Labrecque et al, 2019 ; Puhr et al, 2021 ; Ylitalo et al, 2021 ). For example, the SPP1 gene was identified as an extracellular matrix signature, which was remarkably up-regulated in mCRPC and may be a novel therapeutic target for mCRPC patients ( Pang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In prostate cancer, the glucocorticoid receptor (GR) is a prime suspect for acquired therapy resistance, as resistance to the antiandrogen enzalutamide (Enz) can occur through bypass of androgen receptor (AR) blockade by the glucocorticoid receptor (GR)[ 70 ]. Prostate cancer (PCa) cells are able to increase GR signaling during anti-androgen therapy and thereby circumvent androgen receptor (AR) blockade and cell death [ 71 , 72 ]. In 2014, Dago et al [ 70 ] analyzed the whole-genome CNV variation of peripheral blood CTCs in patients with castration-resistant prostate cancer at four treatment time points, before chemotherapy, before treatment with abiraterone, when symptoms were significantly relieved, and when symptoms worsened.…”
Section: Single Cell Sequencing Of Circulating Tumor Cellsmentioning
confidence: 99%
“…GR expression is silenced in prostate cancer by a combination of AR binding and EZH2-mediated repression at the GR locus but is restored in advanced prostate cancers upon reversion of both repressive signals. Puhr et al [ 72 ] identified MAO-A as a directly upregulated mutual epithelial and stromal GR target, which is induced after GC treatment and during PCa progression. Their findings demonstrate that targeting MAO-A represents an innovative therapeutic strategy to synergistically block GR- and AR-dependent PCa cell growth and thereby overcome therapy resistance.…”
Section: Single Cell Sequencing Of Circulating Tumor Cellsmentioning
confidence: 99%
“…Moreover, a significant difference was observed in the chemotherapy response to the other 83 drugs, although they are not yet approved for the treatment of PRAD. Despite the advances in PRAD treatment, therapeutic options for PRAD remain limited [ 124 , 125 ]. These 83 drugs can be considered a pool when looking for novel therapies.…”
Section: Discussionmentioning
confidence: 99%